Analisis Faktor-Faktor yang Mempengaruhi Keputusan Pelanggan dalam Memilih Jasa Pengiriman Barang (Studi Kasus pada Rentang Umur 17-21 Tahun) - Kinanti, Rafifa Zahra; Purnawan, Purnawan (Jurnal Teknik Industri Terintegrasi (JUTIN), 2025)
The increasing number of online and e-commerce stores and consumer demand shows that delivery services are in high demand. Factors such as affordability, accessibility, speed of delivery, ease of tracking, and service quality influence the selection of delivery services. This study aims to explore the factors that influence consumers' decision to choose a delivery service, including existing factors (price, speed, and service) as well as new factors. In addition, this study also examines the effect of customer loyalty on the performance of delivery service companies. This study used linear regression on a sample of 35 teenage respondents aged 17-21 who had used delivery services. The results show that teenagers are very concerned about various factors in choosing a delivery service, and these factors affect customer loyalty.